Male Breast Cancer Incidence and Mortality Risk in the Japanese Atomic Bomb Survivors – Differences in Excess Relative and Absolute Risk from Female Breast Cancer - Little, Mark P. (Environ Health Perspect, 2016)
BACKGROUND: There are well-known associations of ionizing radiation with female breast cancer, and emerging evidence also for male breast cancer. In the United Kingdom, female breast cancer following occupational radiation exposure is among that set of cancers eligible for state compensation and consideration is currently being given to an extension to include male breast cancer. OBJECTIVES: We compare radiation-associated excess relative and absolute risks of male and female breast cancers. METHODS: Breast cancer incidence and mortality data in the Japanese atomic-bomb survivors were analyzed using relative and absolute risk models via Poisson regression. RESULTS: We observed significant (p ≤ 0.01) dose-related excess risk for male breast cancer incidence and mortality. For incidence and mortality data, there are elevations by factors of approximately 15 and 5, respectively, of relative risk for male compared with female breast cancer incidence, the former borderline significant (p = 0.050). In contrast, for incidence and mortality data, there are elevations by factors of approximately 20 and 10, respectively, of female absolute risk compared with male, both statistically significant (p < 0.001). There are no indications of differences between the sexes in age/time-since-exposure/age-at-exposure modifications to the relative or absolute excess risk. The probability of causation of male breast cancer following radiation exposure exceeds by at least a factor of 5 that of many other malignancies. CONCLUSIONS: There is evidence of much higher radiation-associated relative risk for male than for female breast cancer, although absolute excess risks for males are much less than for females. However, the small number of male cases and deaths suggests a degree of caution in interpretation of this finding. CITATION: Little MP, McElvenny DM. 2017. Male breast cancer incidence and mortality risk in the Japanese atomic bomb survivors – differences in excess relative and absolute risk from female breast cancer. Environ Health Perspect 125:223–229; http://dx.doi.org/10.1289/EHP151